Deconstructing the staged and existential authentic of rurality in Japan - Crowe-Delaney, Lesley (Inderscience Enterprises Ltd, 2018)
Idealised rural lifestyles depicted in Japanese produced TV dramas and movies contrast with the tightly-held traditions and hard work of the real, rural Japan. Furusato (old hometown), fureai (connectedness to each other), and shizen (nature) are concepts assumed lost in urbanisation, an urban-rural dichotomy, becoming tropes in these dramatic 'pseudo-ethnographies', used by government economic and tourism policies designed to repopulate regional Japan. Tourism campaigns encouraging locals to experience Japan are swathed in nationalism. The rural is exemplified as authentic Japan, guardian of values, culture and community and historic components of tourism culture, over time transformed to 21st century staged authenticities. The reimaging of this Japanese rural space then becomes an existential authenticity for the visitor or new community member. Using a human geography lens for the movie, Departures, this paper deconstructs the transformation of staged authenticities into existential ones as visitors become part of the rural space and places.